Human security, changing states and global responses institutions and practices - Bae, Sangmin 1971-; Maruyama, Makoto (Routledge studies in human security, 2015)
This book critically assesses the human security challenges faced by states, focusing on how and to what extent the state is influenced by global structures and operations. Having grown rapidly since the 1990s, the field of human security has spawned a wide variety of academic research. This research has helped to reconceptualize the notion of security, both broadening and deepening it, and it has created a space where unconventional and multidimensional forms of security inform international policy practices. However, while various issues and cases of human security have received growing academic attention and policy interest, many of the existing books on human security focus primarily on non-state actors